The Effects of Thickness Reduction and Particles Sizes on the Properties Graphite - Polypropylene Composite - Selamat, Mohd Zulkefli; Sahari, Jaafar; Muhamad, Norhamidi; Muchtar, Andanastuti (Universiti Malaya, 2011)
Over the past decade, rapid progress has been made in understanding and development of Conductive Polymer Composites (CPC). The deformations through pressing processes of CPC have significant effects on its properties especially electrical conductivity. In this research, focus is given to Polypropylene (PP)-graphite (G) composites. The G with the various sizes (40, 100, 150 and 200 μm) and binder are mixed with ratios of 80:20 according to weight percentage is selected to produce samples. A Rheomix mixer (Haake-PolylabTM) with 50 cm3 mixing chamber was used for composites compounding or mixing process. After that the mixtures were shaped through compression molding to form disc with 25 mm diameter and average thickness of 7.5 mm. The disc was then deformed through pressed with the thickness reduction of 25%, 50% and 75% at the temperatures of 1900C. The related tests such as conductivity measurements in the plane direction and microstructure analysis used Scanning Electron Microscope (SEM) have been conducted in determining the effect of thickness reduction on the properties of the disc. The disc with the thickness reduction of 25% has shows good affect on the properties especially the microstructure and the electrical properties. The electrical conductivity has increased between 20% up to 110% as compare to unpress disc.